Size-Adjustable Nano-Drug Delivery Systems for Enhanced Tumor Retention and Penetration - Deng, Miao; Rao, Jing-Dong; Guo, Rong; Li, Man; He, Qin (Pharmaceutical Fronts, 2021)
Over the past decades, nano-drug delivery systems have shown great potential in improving tumor treatment. And the controllability and design flexibility of nanoparticles endow them a broad development space. The particle size is one of the most important factors affecting the potency of nano-drug delivery systems. Large-size (100–200 nm) nanoparticles are more conducive to long circulation and tumor retention, but have poor tumor penetration; small-size (<50 nm) nanoparticles can deeply penetrate tumor but are easily cleared. Most of the current fixed-size nanoparticles are difficult to balance the retention and penetration, while the proposal of size-adjustable nano-drug delivery systems offers a solution to this paradox. Many endogenous and exogenous stimuli, such as acidic pH, upregulated enzymes, temperature, light, catalysts, redox conditions, and reactive oxygen species, can trigger the in situ transformation of nanoparticles based on protonation, hydrolysis, click reaction, phase transition, photoisomerization, redox reaction, etc. In this review, we summarize the principles and applications of stimuli-responsive size-adjustable strategies, including size-enlargement strategies and size-shrinkage strategies. We also propose the challenges faced by size-adjustable nano-drug delivery systems, hoping to promote the development of this strategy.
Keywords: size-adjustable; nano-drug delivery systems; stimuli-responsive; tumor retention; tumor penetration